Efeito de ácidos orgânicos ou monensina sódica sobre a fermentação ruminal - Silveira, Alisson Minozzo da (2013)
Food additives are substances that control animal metabolism, increasing the efficiency of feed utilization and providing greater animal production. Monensin is certainly the most studied and used, but in recent years its use has undergone several constraints, mainly by the European Union and the United States, so it is crucial to study new alternatives which present satisfactory results additives on animal performance. Thus, an experiment was conducted evaluating, by the in vitro gas technique, the use of a product based on organic acids compared to monensin. Four treatments were used: CTL (no additives), MON (monensin) and CTX 250 and 500 (250 and 500ppm organic additive)with four replications in a completely randomized design with repeated measures in time. Were evaluated the parameters of gas production, production of short chain fatty acids (SCFA), methane (CH4), ammoniacal nitrogen (NH3-N) and pH. MON treatment increased (P <0.05) propionate production and decreased (P <0.05) gas production, CH4, acetate, butyrate, valerate, isobutyrate, isovalerate, the ratio of acetate/propionate and SCFA total production relative to CTL, not changing the NH3-N concentration. Treatments with organic acids 250 and CTX 500, CTX 500 only showed a decrease in the concentrations of NH3-N, the other parameters showed no significant changes (P >0.05) with the addition of organic acids in relation to CTL. In this sense the monensin presents characteristics of modulation rumen environment.